Road salt compromises functional morphology of larval gills in populations of an amphibian. - Szeligowski, Richard V.; Scanley, Jules A.; Broadbridge, Christine C.; Brady, Steven P. (Environmental pollution (Barking, Essex : 1987), 2021)
Across the planet, winter de-icing practices have caused secondary salinization of freshwater habitats. Many amphibians are vulnerable because of permeable skin and reliance on small ponds, where salinity can be high. Early developmental stages of amphibians are especially sensitive to salt, and larvae developing in salt-polluted environments must osmoregulate through ion exchange in gills. Though ionoregulation in amphibian gills is generally understood, the role of gill morphology remains poorly described. Yet gill structure should affect ionoregulatory capacity, for instance in terms of available surface area. As larval amphibian gills also play critical roles in gas exchange and foraging, changes in gill morphology from salt pollution potentially affect not only osmoregulation, but also respiration and feeding. Here, we used an exposure experiment to quantify salinity effects on larval gill morphology in wood frogs (Rana sylvatica). We measured a suite of morphological traits on gill tufts—where ionoregulation and gas exchange occur—and on gill filters used in feeding. Larvae raised in elevated salinity developed larger gill tufts but with lower surface area to volume ratio. Epithelial cells on these tufts were less circular but occurred at higher densities. Gill filters showed increased spacing, likely reducing feeding efficiency. Many morphological gill traits responded quadratically, suggesting that salinity might induce plasticity in gills at intermediate concentrations until energetic demands exceed plasticity. Together, these changes likely diminish ionoregulatory and respiratory functionality of gill tufts, and compromise feeding functionality of gill filters. Thus, a singular change in aquatic environment from a widespread pollutant appears to generate a suite of consequences via changes in gill morphology. Critically, these changes in traits likely compound the severity of fitness impacts in populations dwelling in salinized environments, whereby ionoregulatory energetic demands should increase respiratory and foraging demands, but in individuals who possess structures poorly adapted for these functions. © 2021 Elsevier Ltd
2 citations (Crossref) [2023-10-31]
Keywords: Amphibia; Animals; Article; Feeding; Freshwater habitats; Functional morphology; Gas exchange; Gill morphology; Gills; Humans; Ion exchange; Larva; Morphology; Osmoregulation; Osmosis; Osmotic stress; Plasticity; Pollution; Rana sylvatica; Ranidae; Road effect; Road salts; Roads and streets; Salinisation; Secondary salinization; Sodium Chloride; Surface area; amphibian; animal; animal cell; animal experiment; animal tissue; aquatic environment; breathing; cell density; cell structure; controlled study; dept.bio; developmental stage; embryo; energetic demand; energy; epithelium cell; exposure; foraging; functional morphology; gill; gill filter; gill length; gill tuft; human; larva; length; nonhuman; osmoregulation; peer-reviewed; plasticity; pollution exposure; road; salinity; salinization; salt; sodium chloride; surface area; volume

Waste Citrus reticulata Assisted Preparation of Cobalt Oxide Nanoparticles for Supercapacitors - Srivastava, Rishabh; Bhardwaj, Shiva; Kumar, Anuj; Singhal, Rahul; Scanley, Jules; Broadbridge, Christine C.; Gupta, Ram K. (Nanomaterials, 2022)
The green, sustainable, and inexpensive creation of novel materials, primarily nanoparticles, with effective energy-storing properties, is key to addressing both the rising demand for energy storage and the mounting environmental concerns throughout the world. Here, an orange peel extract is used to make cobalt oxide nanoparticles from cobalt nitrate hexahydrate. The orange peel extract has Citrus reticulata, which is a key biological component that acts as a ligand and a reducing agent during the formation of nanoparticles. Additionally, the same nanoparticles were also obtained from various precursors for phase and electrochemical behavior comparisons. The prepared Co-nanoparticles were also sulfurized and phosphorized to enhance the electrochemical properties. The synthesized samples were characterized using scanning electron microscopic and X-ray diffraction techniques. The cobalt oxide nanoparticle showed a specific capacitance of 90 F/g at 1 A/g, whereas the cobalt sulfide and phosphide samples delivered an improved specific capacitance of 98 F/g and 185 F/g at 1 A/g. The phosphide-based nanoparticles offer more than 85% capacitance retention after 5000 cycles. This study offers a green strategy to prepare nanostructured materials for energy applications.
3 citations (Crossref) [2023-10-31] Number: 23
Keywords: Citrus reticulata; Co_3O_4 nanoparticles; characterization; charge storage; dept.phy; peer-reviewed; supercapacitors

Combinatorial Strategies for Synthesis and Characterization of Alloy Microstructures over Large Compositional Ranges. - Li, Yanglin; Jensen, Katharine E; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Scanley, B Ellen; Broadbridge, Christine C; Schroers, Jan (ACS combinatorial science, 2016)
The exploration of new alloys with desirable properties has been a long-standing challenge in materials science because of the complex relationship between composition and microstructure. In this Research Article, we demonstrate a combinatorial strategy for the exploration of composition dependence of microstructure. This strategy is comprised of alloy library synthesis followed by high-throughput microstructure characterization. As an example, we synthesized a ternary Au-Cu-Si composition library containing over 1000 individual alloys using combinatorial sputtering. We subsequently melted and resolidified the entire library at controlled cooling rates. We used scanning optical microscopy and X-ray diffraction mapping to explore trends in phase formation and microstructural length scale with composition across the library. The integration of combinatorial synthesis with parallelizable analysis methods provides a efficient method for examining vast compositional ranges. The availability of microstructures from this vast composition space not only facilitates design of new alloys by controlling effects of composition on phase selection, phase sequence, length scale, and overall morphology, but also will be instrumental in understanding the complex process of microstructure formation in alloys.
19 citations (Crossref) [2023-10-31] Place: United States Li, Yanglin. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Li, Yanglin. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Jensen, Katharine E. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Liu, Yanhui. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Liu, Yanhui. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Liu, Jingbei. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Gong, Pan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Scanley, B Ellen. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, United States. Broadbridge, Christine C. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, United States. Schroers, Jan. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States.
Keywords: *Alloys/ch [Chemistry]; *Combinatorial Chemistry Techniques/mt [Methods]; *Copper/ch [Chemistry]; *Gold/ch [Chemistry]; *Silicon/ch [Chemistry]; Alloys; Combinatorial Chemistry Techniques; Copper; Gold; High-Throughput Screening Assays; Materials Testing; Physical Phenomena; Silicon; alloy; alloy microstructure; chemistry; combinatorial chemistry; combinatorial materials science; copper; dept.phy; gold; high throughput screening; high-throughput; materials testing; phase mapping; physical phenomena; procedures; silicon

Noble metal high entropy alloys - Sohn, Sungwoo; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Prades-Rodel, Silke; Blatter, Andreas; Scanley, B. Ellen; Broadbridge, Christine C.; Schroers, Jan (Scripta Materialia, 2017)
A series of noble metal high entropy alloys with up to six constituent elements has been produced by casting. PtPdRhIrCuNi forms single-phase face-centered cubic solid solution, and its stability is confirmed by annealing experiments. This alloy deforms homogeneously to ~30% to a high ultimate compression strength of 1839MPa. We discuss rules for the formation of single-phase solid solution.
70 citations (Crossref) [2023-10-31]
Keywords: Annealing experiments; Compressive properties; Compressive property; Constituent elements; Entropy; FCC structure; Face-centered cubic; Fcc structures; High entropy alloys; Phase stability; Precious metals; Single phase; Solid solution; Solid solutions; Ultimate compression; dept.phy

Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing. - Bordeenithikasem, Punnathat; Liu, Jingbei; Kube, Sebastian A; Li, Yanglin; Ma, Tianxing; Scanley, B Ellen; Broadbridge, Christine C; Vlassak, Joost J; Singer, Jonathan P; Schroers, Jan (Scientific reports, 2017)
The glass forming ability (GFA) of metallic glasses (MGs) is quantified by the critical cooling rate (R C). Despite its key role in MG research, experimental challenges have limited measured R C to a minute fraction of known glass formers. We present a combinatorial approach to directly measure R C for large compositional ranges. This is realized through the use of compositionally-graded alloy libraries, which were photo-thermally heated by scanning laser spike annealing of an absorbing layer, then melted and cooled at various rates. Coupled with X-ray diffraction mapping, GFA is determined from direct R C measurements. We exemplify this technique for the Au-Cu-Si system, where we identify Au56Cu27Si17 as the alloy with the highest GFA. In general, this method enables measurements of R C over large compositional areas, which is powerful for materials discovery and, when correlating with chemistry and other properties, for a deeper understanding of MG formation.
44 citations (Crossref) [2023-10-31] Place: England Bordeenithikasem, Punnathat. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Kube, Sebastian A. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Li, Yanglin. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Ma, Tianxing. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Vlassak, Joost J. School of Engineering and Applied Science, Harvard University, Cambridge, Massachusetts, 02138, USA. Singer, Jonathan P. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. jan.schroers@yale.edu. Erratum in (EIN)
Keywords: dept.phy; peer-reviewed

Synthesis and characterization of CuS, CuS/graphene oxide nanocomposite for supercapacitor applications - Singhal, Rahul; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Sharma, Rakesh K. (AIP Advances, 2020)
Supercapacitors or electrochemical capacitors are receiving greater interest because of their high-power density, long life, and low maintenance. We have synthesized CuS nanoparticles and graphene oxide (CuS-GO) nanocomposites for supercapacitor applications because of their low cost and excellent electrochemical properties. The phase purity of each material was determined using powder XRD studies. The bandgap was determined by UV-visible spectrophotometric studies. Scanning electron microscope and transmission electron microscope images revealed the nano-scale morphology of the synthesized particles. All the electrochemical measurements were conducted in a standard three-electrode configuration, using a platinum wire as the counter electrode and Hg/HgO as the reference electrode. CuS and its composites with graphene oxide on nickel foam were used as working electrodes. All the electrochemical measurements were performed in 3M KOH solution. The CuS-GO nanocomposite electrode showed a specific capacitance of 250 F/g, 225 F/g, 182 F/g, 166 F/g, 161 F/g, and 158 F/g at a current density of 0.5 A/g, 1 A/g, 5 A/g, 10 A/g, 15 A/g, and 20 A/g, respectively. CuS-GO electrodes showed a specific capacitance retention of 70% after 5000 charge-discharge cycles at a current density of 5 A/g. © 2020 Author(s).
19 citations (Crossref) [2023-10-31] WOS:000519123100001
Keywords: Capacitance; Charge-discharge cycle; Copper compounds; Electric discharges; Electrochemical capacitor; Electrochemical electrodes; Electrochemical measurements; Foams; Graphene; Mercury compounds; Nanocomposite electrodes; Nanocomposites; Potassium hydroxide; Scanning electron microscopy; Spectrophotometric study; Supercapacitor; Supercapacitor application; Synthesis (chemical); Synthesis and characterizations; Transmission electron; Transmission electron microscopy; dept.phy; peer-reviewed

Effect of reduce graphene oxide (Rgo) on electrochemical performance of Cus for supercapacitor applications - Singhal, Rahul; Thorne, David; Chaudhary, Manika; Bhardwaj, Shiva; Abazi, Rilind; Gupta, Ram K.; Scanley, Jules; Broadbridge, Christine C.; Singh, B. P.; LeMaire, Peter K.; Sharma, Rakesh K. (2023)
CuS and CuS-rGO nanocomposites were synthesized by the hydrothermal method. The synthesized CuS and rGO-CuS nanocomposite materials were physically characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) and were evaluated electrochemically for supercapacitor applications. The specific capacitance of CuS was determined to be 207 F/g, 150 F/g, and 97 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350 F/g, 251 F/g, and 149 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively.
Keywords: CuS; SEM; Supercapacitors; dept.phy; rGO; specific capacitance

Study of MnO2-Graphene Oxide nanocomposites for supercapacitor applications - Singhal, Rahul; Fagnoni, Justin; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Manivannan, Mani; Pandey, Rishikesh (MRS Advances, 2019)
Graphene oxide (GO)/MnO2 nanocomposites were synthesized by adding KMnO4 in a solution of water and ethanol (3:1), containing 10 mg of GO. Brown precipitates were obtained after a continuous stirring for 1 hr. The precipitates were then washed with deionized water (DI) water and dried to obtain the MnO2-GO nanocomposites. Pure MnO2 was also synthesized using the same method without GO for the comparison. X-ray diffraction pattern confirm δ-MnO2 type of MnO2 with birnessite type MnO2 structure. The TEM images show the average diameter of MnO2 nanorods as 15 nm. Electrochemical characterizations were carried out in an aqueous solution of 3M KOH. Charge-discharge studies were carried out between 1A/g to 20 A/g current range. The MnO2-GO nanocomposites showed improved electrochemical performances. The capacitance of MnO2 and MnO2-GO electrodes was found to be as 300 F/g, and 350 F/g, respectively at a current of 0.5 A/g. © 2019 Materials Research Society.
6 citations (Crossref) [2023-10-31]
Keywords: Average diameter; Charge-discharge; Continuous stirrings; Current range; Deionized water; Electric discharges; Electrochemical characterizations; Electrochemical performance; Energy storage; Graphene; Graphene oxide nanocomposites; Manganese oxide; Nanocomposites; Nanorods; Potassium hydroxide; Raman spectroscopy; Supercapacitor; Supercapacitor application; X ray diffraction; dept.phy; energy storage; graphene; peer-reviewed; x-ray diffraction (XRD)

Combinatorial development of antibacterial Zr-Cu-Al-Ag thin film metallic glasses. - Liu, Yanhui; Padmanabhan, Jagannath; Cheung, Bettina; Liu, Jingbei; Chen, Zheng; Scanley, B Ellen; Wesolowski, Donna; Pressley, Mariyah; Broadbridge, Christine C; Altman, Sidney; Schwarz, Udo D; Kyriakides, Themis R; et al. (Scientific Reports, 2016)
Metallic alloys are normally composed of multiple constituent elements in order to achieve integration of a plurality of properties required in technological applications. However, conventional alloy development paradigm, by sequential trial-and-error approach, requires completely unrelated strategies to optimize compositions out of a vast phase space, making alloy development time consuming and labor intensive. Here, we challenge the conventional paradigm by proposing a combinatorial strategy that enables parallel screening of a multitude of alloys. Utilizing a typical metallic glass forming alloy system Zr-Cu-Al-Ag as an example, we demonstrate how glass formation and antibacterial activity, two unrelated properties, can be simultaneously characterized and the optimal composition can be efficiently identified. We found that in the Zr-Cu-Al-Ag alloy system fully glassy phase can be obtained in a wide compositional range by co-sputtering, and antibacterial activity is strongly dependent on alloy compositions. Our results indicate that antibacterial activity is sensitive to Cu and Ag while essentially remains unchanged within a wide range of Zr and Al. The proposed strategy not only facilitates development of high-performing alloys, but also provides a tool to unveil the composition dependence of properties in a highly parallel fashion, which helps the development of new materials by design.
51 citations (Crossref) [2023-10-31] Place: England Liu, Yanhui. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Liu, Yanhui. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Padmanabhan, Jagannath. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Padmanabhan, Jagannath. Department of Biomedical Engineering, Yale University, New Haven CT 06511, USA. Cheung, Bettina. Department of Biomedical Engineering, Yale University, New Haven CT 06511, USA. Liu, Jingbei. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Chen, Zheng. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Chen, Zheng. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Wesolowski, Donna. Department of Molecular, Cellular and Developmental Biology, Yale University, New Haven CT 06520, USA. Pressley, Mariyah. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Broadbridge, Christine C. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Altman, Sidney. Department of Molecular, Cellular and Developmental Biology, Yale University, New Haven CT 06520, USA. Schwarz, Udo D. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Schwarz, Udo D. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Schwarz, Udo D. Department of Chemical and Environmental Engineering, Yale University, New Haven CT 06520, USA. Kyriakides, Themis R. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Kyriakides, Themis R. Department of Biomedical Engineering, Yale University, New Haven CT 06511, USA. Kyriakides, Themis R. Department of Pathology, Yale University, New Haven CT 06520, USA. Schroers, Jan. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA.
Keywords: *Alloys/ch [Chemistry]; *Aluminum/ch [Chemistry]; *Anti-Bacterial Agents/ch [Chemistry]; *Combinatorial Chemistry Techniques; *Silver/ch [Chemistry]; Alloys; Alloys/pd [Pharmacology]; Aluminum; Anti-Bacterial Agents; Anti-Bacterial Agents/pd [Pharmacology]; Combinatorial Chemistry Techniques; Copper; Copper/ch [Chemistry]; Escherichia coli; Escherichia coli/de [Drug Effects]; Escherichia coli/gd [Growth & Development]; Escherichia coli/ul [Ultrastructure]; Glass; Glass/ch [Chemistry]; Microscopy; Atomic Force; Silver; Structure-Activity Relationship; Zirconium; Zirconium/ch [Chemistry]; alloy; aluminum; antiinfective agent; atomic force microscopy; chemistry; combinatorial chemistry; copper; dept.phy; drug effect; glass; growth; development and aging; peer-reviewed; silver; structure activity relation; ultrastructure; zirconium